Infra-red Spectral Investigations on 2,4-Dinitrophenyl Hydrzine - Karunanidhi, N.; Varadhan, S.R.; Gunasekaran, S. (Asian Journal of Chemistry, 2010)
In this work, we report an analysis of vibrational spectrum of 2,4-dinitrophenyl hydrazine. Infrared spectrum of 2,4-dinitrophenyl hydrazine has been recorded in the region of 4000–400 cm–1. The spectrum of this reagent has been analysed on the basis of Cs symmetry.